Inclusivity in neo-liberal policy environment: preparedness of mass media to support disability awareness campaigns in Ghana. Issue 21 (8th October 2020) - Amoako, Seth; Opoku, Maxwell Peprah; Nketsia, William; Edusei, Anthony Kweku; Afriyie, Sally Adwoa; Badu, Eric
Abstract: Purpose: The mass media have been described as an important institution in educating society about persons with disabilities and in facilitating their acceptance. However, calls to project a positive public image of persons with disabilities and to develop an inclusive society have coincided with the neo-liberal approach to policymaking, whereby government plays a minimised role in the provision of basic services to citizens. Although the extant literature from advanced countries has found stereotypical and disempowering portrayals of persons with disabilities in the mass media, this area remains unresearched in developing countries. The purpose of this study was to explore how the managers of media organisations conceptualise disability, their perception of the role and contribution of the media towards promoting effective public awareness campaigns about persons with disabilities. Methods: This descriptive, qualitative study draws on a purposive sample of 20 participants consisting of general managers, news editors and programme managers from ten media organisations in a region in Ghana. A semi-structured interview guide was developed from the literature, which included tenets of neo-liberalism, to collect the data. Results: The study found that the majority of respondents cited medical model explanations of disability. Also, they were unprepared to prioritise disability issues due to lack of public interest in disability programmes and lack of funds and sponsorship for disability programmes. Conclusion: Governments must offer tax rebates to media organisations to enable them to prioritise disability issues. Other recommendations for developing media interest in disability issues are also discussed. Implications for rehabilitation: This study shows limited understanding of disability among decision-makers or key players in media organisations in Ghana. In an environment of meritocracy, persons with disabilities who struggle to access education in Ghana, may be unable to secure jobs at media organisation. This study shows that media organisations seem unprepared to support or project image of persons with disabilities because such ventures come with no reward. We conclude that if the government is committed towards achieving an inclusive society in Ghana, it could offer tax rebate to media organisations to enable them cover disability programmes.